2020
DOI: 10.3390/rs12060992
|View full text |Cite
|
Sign up to set email alerts
|

Signal Extraction from GNSS Position Time Series Using Weighted Wavelet Analysis

Abstract: The daily position time series derived by Global Navigation Satellite System (GNSS) contain nonlinear signals which are suitably extracted by using wavelet analysis. Considering formal errors are also provided in daily GNSS solutions, a weighted wavelet analysis is proposed in this contribution where the weight factors are constructed via the formal errors. The proposed approach is applied to process the position time series of 27 permanent stations from the Crustal Movement Observation Network of China (CMONO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The other group includes empirical mode decomposition (EMD), ensemble empirical mode decomposition (EEMD) and multivariate empirical mode decomposition (MEMD), etc. [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The other group includes empirical mode decomposition (EMD), ensemble empirical mode decomposition (EEMD) and multivariate empirical mode decomposition (MEMD), etc. [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The trend, annual and semiannual signals are usually estimated by the least-squares fitting. The other spatiotemporal signals are more effectively extracted and analyzed with some classic signal analysis methods, such as wavelet analysis (WA) [ 8 , 9 , 10 ], Kalman filter (KF) [ 11 , 12 ], empirical orthogonal function (EOF) [ 13 ], singular spectrum analysis (SSA) [ 14 , 15 ], and principal component analysis (PCA) [ 16 , 17 , 18 , 19 ]. Among these methods, PCA is one of the data-driven multivariate approaches based on second-order statistics (variance and covariance) and isolates the underlying sources without any prior knowledge [ 7 ], which implicitly assumes that a GNSS time series is polluted only by multivariate Gaussian noise.…”
Section: Introductionmentioning
confidence: 99%
“…To retrieve the seasonal signals of GNSS coordinate time series, several methods have been investigated by numerous scholars during the past several decades [3,4,[11][12][13][14][15][16][17][18]. A detailed review can be found in [19].…”
Section: Introductionmentioning
confidence: 99%